Theoretical analysis and synthesis of Al4O4C and Al2CO phase in the resin bonded Al-Al2O3 refractory in N2-flowing. Issue 2 (1st February 2018) - Yan, Mingwei; Li, Yong; Li, Hongyu; Sun, Jialin
Abstract: In flowing nitrogen, Al4 O4 C and Al2 CO bonded Al2 O3 -based composite was successfully prepared by a gaseous phase mass transfer pathway at 1600 °C for 3 h after an Al-AlN core-shell structure was formed in the resin bonded Al-Al2 O3 refractory at 580 °C for 8 h. The formation mechanism of Al4 O4 C and Al2 CO phase is as follows. An Al-AlN core–shell structure is built at 580 °C for 8 h and broken at higher temperatures, and then, Al(g) reacts with C from the resin and N2 to form Al4 C3 and AlN, respectively. Owing to the exothermic reaction of the Al4 C3 and AlN formation, the reaction temperature in the resin bonded Al-Al2 O3 refractory is above the practical environmental temperature; for instance, the reaction temperature is above 1715 °C at 1600 °C in this work. Therefore, Al4 C3 reacts with Al2 O3 to generate Al4 O4 C and then Al4 O4 C is transformed into Al2 OC by the reaction Al 4 O 4 C ( s ) + Al 4 C 3 ( s ) → 4Al 2 OC ( s ) at elevated temperatures. Al2 OC solid solution is finally formed through the dissolution of AlN into Al2 OC.